Increased CD14+HLA-DR−/low Myeloid-Derived Suppressor Cells Correlate With Disease Severity in Systemic Lupus Erythematosus Patients in an iNOS-Dependent Manner - Wang, Zhitao; Zhu, Fengfeng; Wang, Jiyu; Tao, Qianshan; Xu, Xuanxuan; Wang, Huiping; Xiong, Shudao; Wang, Yiping; Zhai, Zhimin (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) comprise of a population of cells, which suppress the innate and adaptive immune system via different mechanisms. MDSCs are accumulated under pathological conditions. The present study aimed to clarify the pathological role of MDSCs in systemic lupus erythematosus (SLE) patients. Consequently, the level of circulating M-MDSCs was significantly increased in newly diagnosed SLE patients as compared to healthy controls. An elevated level of M-MDSCs was positively correlated with the disease severity in SLE patients and an immunosuppressive role was exerted in an iNOS-dependent manner. The decrease in the number of M-MDSCs after therapy rendered them as an indicator for the efficacy of treatment. These results demonstrated that M-MDSCs participated in the pathological progress in SLE patients. Thus, MDSCs are attractive biomarkers and therapeutic targets for SLE patients.